Exploring the Barriers to Access and Utilization of Healthcare Services Faced by the Transgender Population of Rawalpindi, Pakistan - Rashid, Zubaida; Mashhadi, Syed Fawad; Fatima, Urooj; Noor, Irbah; Javaid, Fahad; Najm, Muhammad; Yasin, Talha (Pakistan Armed Forces Medical Journal, 2024)
Objective: To explore the barriers and disparities in receiving healthcare faced by Transgender population of Rawalpindi,Pakistan.Study Design: Qualitative study.Place and Duration of Study: Study was conducted in Rawalpindi Pakistan, for a period of 3 months, from Jun to Aug 2022.Methodology: A total of 15 participants were selected via Snowball Sampling technique. An interview guide was generated and semi structured interviews were conducted via telephone calls to explore and understand the discrepancies faced by this population regarding good quality healthcare. Each interview was 30-40 minutes long. The data was collected till saturation and then analyzed by 'thematic analysis’ to generate themes and subthemes.Results: Based on the data, 6 themes highlighting the barriers to quality healthcare faced by trans-genders were identified. The themes were as follows: (1) Structural, (2) Financial, (3) Social, (4) Cognitive, (5) Educational, and (6) Religious/Cultural.Conclusion: The healthcare barriers identified were mainly financial as certain services were costly, religious beliefs which influenced the use of services like hormone replacement therapies, social stigma and lack of support, level of education and poor employment. Stigmatization by the community and healthcare providers was also seen. Thus, it was felt that there were limited awareness campaigns to empower transgender population and for the general population including healthcare workers to be more aware and accepting towards transgender healthcare.